Enabling leagility through IT capabilities and information sharing in Iraqi manufacturing SMEs: Evidence from a PLS-SEM approach - Dirawi, Ammar Nazar Mustafa Al; Khudari, Mohamed; Daud, Salina (Edelweiss Applied Science and Technology, 2025)
Research on leagility, the integration of lean and agile supply chains, is limited, especially in developing nations, and is primarily qualitative in nature. The impact of IT capabilities and their interplay with information exchange in promoting leagility lacks empirical substantiation. This study investigates the impact of IT capabilities (IT infrastructure, IT human resources, and IT integration) on leagility, along with the moderating influence of information sharing. Utilizing the resource-based approach and resource dependence theory, data were collected from a cross-sectional study involving 381 senior managers in Iraqi manufacturing SMEs. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (PLS-SEM). The findings demonstrate that IT capacity and its elements have a favorable impact on leagility. Furthermore, information sharing moderates the impact of IT capacity and its components—IT infrastructure and IT integration—on leagility, but not on IT human resources. This study enhances the Resource-Based View (RBV) and Resource Dependence Theory (RDT) by empirically illustrating how internal IT investments and external collaboration collectively promote resilience in resource-limited contexts. The findings emphasize the necessity for Iraqi SMEs to focus on IT integration and personnel development while utilizing information sharing to enhance supply chain agility performance.